Achieving social justice through hybrid rural and urban model of community based tourism: A conceptual framework / Nuraisyah Chua Abdullah and Ramzyzan Ramly - Chua Abdullah, Nuraisyah; Ramly, Ramzyzan (UiTM Press, 2016)
The governments of many countries have identified Community Based Tourism (CBT) in rural tourism as a catalyst for the development of rural community. Urban poverty in many countries including Malaysia and Cambodia is due to rural-urban migration. The natural population growth in urban areas is an increasingly visible phenomenon in these countries. Hence, this paper aims to suggest the inclusion of the existing concept of community based tourism (CBT) into the urban setting as a supplement to the existing concept, which is dominant in the rural setting. Using Malaysia and Cambodia as a case study, it is the contention of this paper that the hybrid rural and urban community based tourism would better facilitate social justice in tourism destinations.